http://www.when(underbar)is (underbar)enough(underbar)enough?.com. - Palma, Paul de (American Scholar)
Discusses the author's view on microcomputers. Opposition to the view of Roger Schank, a computer science professor at Yale, that most people do not need to own computers; Objections to the ideology that surrounds a computer; Distressing aspect of the media attention paid to the glories of technology.